A stress intensity factor estimation method for the kinked crack under anti-plane load. (February 2018) - Li, Yufei; Sun, Tao; Tian, Yongsheng; Gao, Qing; Tan, Chunqing
Highlights: A more accurate expression for estimating mode III SIF is presented. The expression was modified by conformal mapping and weight function method. The estimated SIF were compared to analytical result and shows a good agreement. Abstract: A method to estimate the mode III stress intensity factor (SIF) of kinked crack under anti-plane load is presented. The SIF of the kinked crack can be estimated by an expression derived from the stress field series of the original crack include first three order terms by the weight function (WF) method. The coefficients of the WFs were obtained by a fitting procedure based on the solutions of the weight function problem, which were solved by a conformal mapping method. The influence of the WFs in the estimation was evaluated as a function of the kink angle and the kink length ratio. The application to the case of a kinked crack shows good agreement with the analytical results.